Between a risk society and a welfare state: social risk resilience and vulnerability to poverty in Lithuania - Navickė, Jekaterina (Socialinė teorija, empirija, politika ir praktika, 2015)
This paper looks into the role the tax-benefit system plays in mitigating widespread socio-economic risks and individual vulnerability to poverty. The drivers behind the changing role of the risk-mitigating social policies are analysed looking through the theoretical lenses of the risk society. The performance of the tax-benefit system in providing a safety net against income loss in cases of unemployment and childbirth is evaluated using the stress-testing approach proposed by Atkinson (2009). The method is applied on a Lithuanian case using the microsimulation model EUROMOD for a period of 2007-2012. The analysis suggests that the role of the welfare state shifts towards promotion of individual responsibility for risk management. The welfare state policies can produce substantially different levels of vulnerability to poverty among population groups facing different risks. In the context of the recent economic crisis in Lithuania, the protection provided by the welfare state declined, while the traditional mutual support among the household members played a major role in the risk management process.